A bridge over troubled water? Celebrities in journalism connecting implicit and institutional politics. (February 2014) - Ahva, Laura; Heikkilä, Heikki; Siljamäki, Jaana; Valtonen, Sanna
This article looks empirically into how audience members evaluate celebrities in journalism; whether and how celebrities help them to envisage their relationship to politics and media and consequently regard themselves as citizens. The analysis generates a broad and audience-based understanding of celebrities in nine focus group discussions, wherein more than 50 citizens in Finland discussed their favourite celebrities. The discussions revealed three interpretative frames explaining what the celebrities represent to the participants: normative, critical and alternative. In the first two, the groups impose a critical view on celebrities, whereas only the latter one comes close to the optimistic view on democratizing the potential of celebrities. Empirically, however, it emerges 'behind' the normative and critical frames and proves to be the weakest. This suggests that celebrities' potential as a means to address alternative or implicit politics is recognized but not actively utilized by citizens.